2004
DOI: 10.1007/s00424-004-1337-7
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of multi-functional somatotropes, mammotropes and gonadotropes of the mouse anterior pituitary

Abstract: The existence of bihormonal anterior pituitary (AP) cells co-storing growth hormone and either prolactin (mammosomatotrope) or gonadotropins (somatogonadotrope) has been described. These cells have been proposed to be involved in "paradoxical" secretion [secretion of an AP hormone induced by a non-related hypothalamic releasing factor (HRH) and transdifferentiation (a phenotypic switch between different cell types without cell division]. Here we combine calcium imaging (to assess HRH responsiveness) and multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Studies have shown that the pituitary contains multipotential precursor cells capable of differentiation later in gestation [49]. There is evidence of plasticity, transdifferentiation, and polyhormonal cells in many pituitary cell types [34,[50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the pituitary contains multipotential precursor cells capable of differentiation later in gestation [49]. There is evidence of plasticity, transdifferentiation, and polyhormonal cells in many pituitary cell types [34,[50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…The function of each lineage is considered as mutually exclusive and under the control of a corresponding set of discrete hypothalamic/pituitary regulatory circuits (Davis et al, 2013;Kelberman et al, 2009;Zhu et al, 2007). However, scattered reports of pituitary cells co-expressing multiple hormones have suggested that the organization and function of the pituitary may be more complex than commonly appreciated (Childs, 2000;Frawley and Boockfor, 1991;Seuntjens et al, 2002a;Villalobos et al, 2004b) and the prevalence and complexity of 'multi-hormone' cells in the adult anterior pituitary has remained undefined on a systematic and global level. Thus, understanding the compositions and functions of pituitary cell lineages and their relationships to hormone expression warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…These responses, which have not been described in adult gonadotrophs before, are reminiscent of amplitude-modulated, non-oscillatory GnRH responses recorded from immature [28] and cloned pituitary gonadotrophs [29]. Alternatively they could correspond to multi-functional cells, like somato-gonadotrophs, which respond poorly to GnRH [30]. It also remains to be determined if the variation of responses to GnRH within the gonadotroph population is due to intrinsic properties (including the stage of cell maturation or cell cycle).…”
Section: Discussionmentioning
confidence: 99%